Characterization and risk assessment of soil around waste rock heaps affected by acid rock drainage in an abandoned pyrite mining area - Tong, Lizhi; Peng, Xiangqin; Chen, Di; Chen, Yanzhi; Wen, Yong; Wang, Wei; Liu, Xiaowen (Frontiers in Environmental Science, 2022)
Acid rock drainage (ARD) is one of the most serious and potentially lasting environmental issues for the mining industry. Many researchers investigated the impact of ARD on downstream farmland, but few focused on the soil properties change around waste rock heaps. In this study, a total of 119 soil samples were taken around the 35 waste rock heaps which are scattered in 12 mining sites in an abandoned pyrite mining area (Baihe County, Northwest China). Both rainy and dry seasons of ARD were collected from the discharge outlet of each mining site. The bulk levels of potentially toxic elements (PTEs), including As, Cd, Cu, Ni, Cr, Zn, Pb, Fe, Mn, and F, in waste rock, soil, and ARD samples were analyzed. Leaching concentration and chemical speciation of these PTEs in soils were further investigated. The results show that the ARD had very high pollution loads of PTEs both in the rainy season and dry season, continuously exporting pollutants to the surrounding soils. More than 70% of the soil samples were acidic (pH<5.5). The bulk of As in 17 soil surface samples exceeded the risk control limit specified in China (60 mg/kg), while the leaching concentrations of As and other PTEs in soil were far below the regulated limits. According to the sequential extraction results, the residual fraction of As, Cr, Cu, Zn, and Ni in the soil accounted for over 90%, indicating these metals were possibly retained by the silicate matrix. Considering the relatively low bioavailability of PTEs and limited exposure routes, the human health risk of the soil surrounding the waste heap is generally acceptable. This research work provides a more comprehensive understanding of the properties and effects of ARD in the pyrite mining area which is conducive to the development of a sustainable control strategy of environmental pollution in typical mining regions.